2010
DOI: 10.1080/01596300903465419
|View full text |Cite
|
Sign up to set email alerts
|

Imagining the mathematician: young people talking about popular representations of maths

Abstract: This paper makes both a critical analysis of some popular cultural texts about mathematics and mathematicians, and explores the ways in which young people deploy the discourses produced in these texts. We argue that there are particular (and sometimes contradictory) meanings and discourses about mathematics that circulate in popular culture, that young people use these as resources in identity making as (non-)mathematicians, negotiating their meaning in ways that are not always predictable, and that their infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 9 publications
3
36
0
Order By: Relevance
“…The notion of the scientist as a brilliant (if eccentric) genius has also been noted in popular stereotypes of mathematicians (Epstein, Mendick, & Moreau, 2010), who observed how often, within young people's views, there is a conflation between being good at mathematics; masculinity; high intelligence; and middle/upper classsness. Moreau et al (in press) also found that 14/15‐year‐old school students differentiated between stereotypical representations of mathematicians (who are short‐haired geniuses) and scientists, who have long, wild hair (“scientists have crazy hair”).…”
Section: “Being a Scientist”: The Scientist As Othersupporting
confidence: 84%
“…The notion of the scientist as a brilliant (if eccentric) genius has also been noted in popular stereotypes of mathematicians (Epstein, Mendick, & Moreau, 2010), who observed how often, within young people's views, there is a conflation between being good at mathematics; masculinity; high intelligence; and middle/upper classsness. Moreau et al (in press) also found that 14/15‐year‐old school students differentiated between stereotypical representations of mathematicians (who are short‐haired geniuses) and scientists, who have long, wild hair (“scientists have crazy hair”).…”
Section: “Being a Scientist”: The Scientist As Othersupporting
confidence: 84%
“…She argued that it is not just their age, but also membership of a community of practice of mathematics undergraduates who shared their views, that enabled this redefinition. While for Nathan, there were more risks of being ostracised ; see also Epstein, Mendick, and Moreau 2010).…”
Section: The Boffin/geek As Abject?mentioning
confidence: 95%
“…Mathematical representation can be presented in visual (e.g., charts, tables, sketches/drawings, and diagrams) and non-visual representations (e.g., mathematical equations and models) (Minarni at al., 2016;Thompson & Chappell, 2007). Numerous studies related to visual representations have been conducted to discuss various problem solving of the word problem (Epstein at al., 2010;Geeslin & Shavelson, 1975;Güler & Author, 2011;Stylianou & Silver, 2009;Thompson & Chappell, 2007;Webel at al., 2016), with additional studies on the use of technology in mathematical representation (Kendal & Stacey, 2003;Ohlsson, 1998;Reilly at al., 1997) and on the elements used to generate relationships in mathematics learning (Moon International Journal of Instruction, July 2018• Vol.11, No.3 at al., 2013. Moreover, mathematical representation research related to socioeconomics has been carried out (Boulton-Lewis & Halford, 1992;Martínez-Sierra at al., 2015;Minibaeva at al., 2016;Moon at al., 2013).…”
Section: Literature Reviewmentioning
confidence: 99%